2014
DOI: 10.1002/2014gl059833
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and optical thickness corrections to diffusive radiative transfer formulations with application to planetary interiors

Abstract: Radiative transfer of high-frequency light under diffusive conditions is key to planetary heat flow and is important in astronomy and engineering. In geophysics, the effective radiative conductivity (k rad ) has been overestimated by threefold due to modeling refraction across planar interfaces as conical emanations of a point source. This assumption violates the second law of thermodynamics because heat can only flow down the thermal gradient. In addition to an extraneous factor of the index of refraction squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
10
2
Order By: Relevance
“…Our mantle k rad estimates are generally similar to previous estimates for olivine polycrystals, although our values are significantly higher at ambient mantle temperature and large grain size (Figure ). On the other hand, our values are much higher at all temperatures than more recent models (e.g., Hofmeister, , , ). Therefore, it may be necessary to reappraise the character of heat transport in a number of important geodynamic settings.…”
Section: Geodynamic Applicationscontrasting
confidence: 75%
See 1 more Smart Citation
“…Our mantle k rad estimates are generally similar to previous estimates for olivine polycrystals, although our values are significantly higher at ambient mantle temperature and large grain size (Figure ). On the other hand, our values are much higher at all temperatures than more recent models (e.g., Hofmeister, , , ). Therefore, it may be necessary to reappraise the character of heat transport in a number of important geodynamic settings.…”
Section: Geodynamic Applicationscontrasting
confidence: 75%
“…Including all effects together in multiphase polycrystalline media results in a complicated problem for which a general effective medium theory is so far unavailable. Moreover, Hofmeister () has suggested that the usual inclusion of n 2 in the source function n 2 I νb (equation ) is fundamentally erroneous, although we dispute this (supporting information section S1).…”
Section: Krad Overviewmentioning
confidence: 68%
“…47 Knowledge of the depth-dependent thermal conductivity of the Earth's mantle would 48 complement recent advances in mantle convection modeling, where a range of possible 49 dynamic structures are predicted using estimated values for the thermal conductivity of 50 the region (Dubuffet et al, 1999;Naliboff and Kellogg, 2006;Tosi et al, 2010). Current 51 estimates of the thermal conductivity of mantle and core materials often rely on 52 extrapolations of experimentally determined values at relatively low pressures and/or 53 temperatures (P-T) (Hofmeister, 1999;Hofmeister, 2010;Hofmeister, 2014) Goncharov et al, 2010). 61…”
Section: Introduction 33mentioning
confidence: 99%
“…We note that this 284 formulation is based on Planck's theory of heat radiation (Planck, 1914), which 285 essentially includes the refractive index of the material (cf. Hofmeister, 2014…”
Section: Introduction 33mentioning
confidence: 99%
“…The following summaries of these chains of conjectures, and of objections to them, are in part abridged from Hamilton (2011Hamilton ( , 2013. Among those who have long raised similar, and other, objections to popular speculations regarding Earth are Anderson (2013), Foulger (2010), Hofmeister (2010Hofmeister ( , 2014, and Hofmeister and Criss (2005, 2012.…”
Section: Earth Obsolete Popular Modelsmentioning
confidence: 97%